Pengaruh Kualitas Audit,Profitabilitas dan Leverage Terhadap Manajemen Laba Riil - Siti Yullaikhah; Listyorini Wahyu Widati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
In Indonesia there are cases where companies manipulate financial statements through profit and loss planning by providing false information. This study aims to examine by finding empirical evidence about the effect of audit quality, profitability and leverage on earnings management through real activities. Real earnings management is an act of engineering earnings carried out by managers outside the normal path to generate profits that are achieved. This type of research is classified as a quantitative type and uses secondary data provided from the Indonesian Stock Exchange website, namely www.idx.co.id. The method in this study was to collect data through purposive sampling which was carried out at manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The number of samples produced was 89 companies according to the criteria multiplied by 3 years of the manufacturing company period. Multiple linear regression is the hypothesis test used in this study. In the research, the results obtained were that the variables of audit quality and profitability had an effect on real earnings management, but the leverage variable had no effect on real earnings management. Keywords : Quality Audit, Profitability, Leverage, Real Earning Management